Uneven power dynamics must be levelled in COVID-19 vaccines access and distribution - Aishat Jumoke Alaran; Yusuff Adebayo Adebisi; Abubakar Badmos; Fahd Khalid-Salako; Sa’id Khalid Gaya; Esther Bosede Ilesanmi; Damilola Quazeem Olaoye; Adeola Bamisaiye; Don Eliseo Lucero-Prisno, III (Public Health in Practice, 2021)
COVID-19 is one of the major global health threats of the 21st century, causing unprecedented humanitarian crises worldwide. Despite concerted efforts to curb the spread of the disease, the pandemic continues to strain healthcare systems globally and a safe, highly effective, and globally acceptable and equitable vaccination program, together with pre-existing precautionary measures, is essential to effectively contain the outbreak. We commented on the need to level any uneven power dynamics in COVID-19 vaccines access and distribution. The COVID-19 vaccines distribution must not allow for sovereignty which is tightly linked to historical imbalances in power and resources to result into discrimination between rich and poor countries. Poor countries must be supported in ensuring access to COVID-19 vaccines by levelling the power dynamics that perpetuate inequality and fuel inequity. We must ensure equity, fairness and transparency in COVID-19 vaccines distribution and gain public trust in COVID-19 vaccines through participatory community engagement. COVID-19 vaccines distribution and access must be equitable and not politicized.